Um estudo do homem ordinário, suas práticas cotidianas e processos de territorialização : migrantes inseridos no contexto do trabalho precário - Vilas Boas, Luana Furtado (2017)
Starting from the perspective of Michel de Certeau in the study of daily life, I sought with this dissertation to understand how the daily practices of territorialization of the ordinary man. The territorialization, in this research, is understood as a complex, systematic and non-linear process, which is possible through daily practices. In this study, the ordinary man is represented by the northeastern worker, a sugarcane cutter who migrates to work in plants in Paraná. I adopted the Life History method for data collection, conducting interviews with seven migrant workers. The analysis was based on the narratives of the interviewees, and through an analytical cut that sought to understand the historical context of life of the and in a constant dialogue with the theories used, I tried to apprehend their daily actions of territorialization. The analysis allowed to identify how much the daily life of these subjects, whether at work, in the city or in the neighborhood, is full of struggles, besides territorial divisions, with constant movements of approximations and distances, divergences and convergences. Thus, in the midst of conformism and resistances, in the daily life of these ordinary men, a tangled up in the formation of networks, in social relations, in practices of convenience, tactics and strategies, can be observed, allowing the resignification of that space and the construction of the territorialization of these workers.